Teaching Proper English to Malaysian Speakers: Focusing on the Vowels, Consonants, Syllable and Stress - Baba, Ricardo (David Publishing, 2013)
The English spoken by a typical Malaysian tends to have a simplified sounds system, which makes the speaker unintelligible to native and other English speakers. This paper discusses the mispronunciations of vowels and consonants, misplaced syllable and improper stress when Malaysians speak in English. This paper also describes the teaching approach used by the author in conducting business communication trainings for both working Malaysians as well as Malaysian students to overcome the mispronunciations and wrong intonation. A survey was conducted among the students who were asked to evaluate the learning and teaching method. The findings indicate that most students rate the quality of the course and the quality of teaching as either 'excellent' or 'good'. The approach is effective among learners who recognize the weaknesses of their spoken English, and are willing to upgrade their intelligibility among native and other non-Malaysian speakers